Prioritizing emerging contaminants in tropical riverine systems: An integrated approach using ecological and human health risk indices - Muhammad Raznisyafiq Razak; Noraishah Mydin Abdul-Aziz; Singh Nisheljeet; Nawaltul Akma Ahmad Sabri; Muhammad Qusyairi Jori Roslan; Nor Rohaizah Jamil; Didi Erwandi Mohamad Haron; Pao-Chi Liao; Ahmad Zaharin Aris (Regulatory Toxicology and Pharmacology, 2026)

Closing the selection gap in passive retrofit optimization: a pathway-based framework for resident-informed selection in old residential buildings in cold-region China - Pengfei Gao; Muhammad Farihan Irfan Mohd. Nor; Mohd Khairul Azhar Mat Sulaiman (Energy and Buildings, 2026)

Population genetics of climbing perch, Anabas testudineus (Bloch, 1792) in the waters of Aceh Province, Indonesia - Nanda Muhammad Razi; Sri Riska Rahayu; Luvi Syafrida Handayani; Mutia Ramadhaniaty; Adrian Damora; Cut Tria Aswina; Putri Khairani Amalia Siregar; Nanda Ulfa Khaira; Muhammad Syukran; Puncak Joyontono; Muhammad Nasir; Nur Fadli; et al. (Ecological Genetics and Genomics, 2026)

Impact of Land Use Change on Water Quality: Toward Sustainable Ecosystem Management in the Nenggiri River Basin - Ismafatin Nabilah Ismail; Mohd Khairul Amri Kamarudin; Mohamad Hafis Amat Simin; Asmawi Ibrahim; Wan Nor Azilawanie Tun Ismail; Ahmad Shakir Mohd Saudi; Mohd Ekhwan Toriman; Sunardi Sunardi; Firdaus Muhammad-Sukki (Water, Air, & Soil Pollution, 2026)

Marine-derived natural products as adaptogens: Enhancing fish resilience to climate and environmental stressors - Ahmad Khusairi Azemi; Nor Hafizah Zakaria; Thirukanthan Chandra Segaran; Yik Sung Yeong; Mazlan Abd Ghaffar; Wong Li Lian; Muhammad Luqman Nordin; Tengku Sifzizul Tengku Muhammad (Regional Studies in Marine Science, 2026)

A scientometric analysis of global sea cucumber original research articles from 1970 to 2023 - Thirukanthan Chandra Segaran; Muhammad Firdaus; Fahrurrozi Fahrurrozi; Fathurrahman Lananan; Huan Gao; Lee Seong Wei; Mohamad Nor Azra; Roslizawati Ab Lah (Marine Environmental Research, 2026)

Synthesis, Physicochemical Characterization and Antibacterial Assessment of Curcumin/2-Hydroxypropyl-β-Cyclodextrin-Functionalized Silver Nanoparticles (cAgNPs) - Amirul Hakim Azmi; Nur Asyura Nor Amdan; Syed Mahmood; Riyanto Teguh Widodo; Muhammad Kumayl Abdulwahab; Zarif Mohamed Sofian (Journal of Pharmaceutical Innovation, 2026)

Impacts of infrastructure development on taxonomic and functional diversity of non-volant small mammals - Ummi Nur Syafiqah Daud; Muhammad Iqbal Md. Jamaluddin; Nor Adibah Ismail; Nurfatin Batrisyia Md. Ali; Noor Fatihah Najihah Arazmi; Norfazliyana Nordin; Saiful Hilmi Jamal Shuhaily; Fudzla Zulfa Khiruddin; Amirul Haikal Zainal; Shukor Md. Nor; Aisah Shukor; Mohammad Saiful Mansor (Biodiversity and Conservation, 2026)

Tailoring subcritical water extraction conditions to enhance antioxidant selectivity from kale (Brassica oleracea var. acephala) - Nurul Faezawaty Jamaludin; Rosnah Shamsudin; Muhammad Hazwan Hamzah; Mohd Zuhair Mohd Nor; Muhamad Yusuf Hasan; Jaturapatr Varith (Innovative Food Science & Emerging Technologies, 2026)

β-radiation exfoliation of LDH nanosheets for next-generation water treatment membranes - Muhammad ‘Adli Nor Azman; Pei Sean Goh; S. Selambakkannu; Yuyang Yao; Ahmad Fauzi Ismail; Khairulnadzmi Jamaluddin; Nur Diyana Suzaimi; Ahmad Syazwan Sahril (Journal of Environmental Chemical Engineering, 2026)

Unveiling Putative Functions of Burkholderia pseudomallei K96243 Hypothetical Proteins Via High-Throughput Characterization of Structural Similarities - Syed Abuthakir Mohamed Husain; Su Datt Lam; Mohd Firdaus-Raih; Sheila Nathan; Nor Azlan Nor Muhammad; Chyan Leong Ng (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Unraveling internal concentration polarization of forward osmosis membrane through β-radiation-exfoliated LDH for heavy metal ion removal - Muhammad 'Adli Nor Azman; Pei Sean Goh; Takaaki Taniguchi; S. Selambakkannu; Yuyang Yao; Ahmad Fauzi Ismail; Khairulnadzmi Jamaluddin; Rendy Muhamad Iqbal (Journal of Water Process Engineering, 2026)

Decoding the cold: integrated secretome profiling reveals extracellular adaptation mechanisms in Glaciozyma antarctica - Shuhaila Mat-Sharani; Farahayu Khairuddin; Nik Yusnoraini Yusof; Norfarhan Mohd-Assaad; Abdul Munir Abdul Murad; Farah Diba Abu Bakar; Nor Muhammad Mahadi; Nurdiana Nordin; Shazilah Kamaruddin (Extremophiles, 2026)

Structural and functional annotation of Glaciozyma antarctica hypothetical proteins using integrated modeling pipelines - Fatin Izzati Abdul Hadi; Doris Huai Xia Quay; Nor Muhammad Mahadi; Mohd Firdaus-Raih; Su Datt Lam (Extremophiles, 2026)

Integrative multi-omics and biochemical validation reveal phenol-to-polyhydroxybutyrate conversion in a palm oil mill effluent microbiome - Izzati Sabri; Siti Suhailah Sharuddin; Mohd Zulkhairi Mohd Yusoff; Nor Azlan Nor Muhammad; Li Sim Ho; Toshinari Maeda; Norhayati Ramli (Journal of Water Process Engineering, 2026)

Recent advances in vaccination strategies against acute hepatopancreatic necrosis disease (AHPND) in shrimp for sustainable aquaculture industry: A comprehensive review - Tijani Isa; Riyanto Teguh Widodo; Suzita Mohd Noor; Nur Asyura Nor Amdan; Zulhisyam Abdul Kari; Norhidayah Mohd Taufek; Fathiah Mohamed Zuki; Alias Abdullah; Subha Bhassu; Zarif Mohamed Sofian; Sagir Mustapha; Didi Erwandi Mohamad Haron; et al. (Fish & Shellfish Immunology, 2026)

Network perspectives on transcriptomic datasets to understand shrimp response mechanisms to environmental and pathogenic stresses: a review - Noorul Darlina Edlin Abd Rahim; Nor Azlan Nor Muhammad; Khor Waiho; Sarahani Harun; Rabiatul-Adawiah Zainal-Abidin; Min Pau Tan; Yeong Yik Sung; Zeti-Azura Mohamed-Hussein; Nor Afiqah-Aleng (Aquaculture International, 2026)

In Silico Identification of MYB Transcription Factors Involved in Mangosteen Anthocyanin and Xanthone Production - Ching-Ching Wee; Masanori Arita; Intan Azlinda Ramlee; Nor Azlan Nor Muhammad; Vijay Kumar Subbiah; Hoe-Han Goh (Tropical Plant Biology, 2026)

Tackling marine pollution in the blue economy: Synergies between wastewater treatment technologies and governmental policies - Setyo Budi Kurniawan; Ali Roziqin; Azmi Ahmad; Mahasin Maulana Ahmad; Benedicta Dian Alfanda; Dwi Sasmita Aji Pambudi; Nor Sakinah Mohd Said; Peer Mohamed Abdul; Muhammad Fauzul Imron (Marine Pollution Bulletin, 2026)

Adaptability of Barbados Blackbelly rams towards elevated temperature-humidity index assessed through reproductive physiology and behaviour - Muhammad Syafiq Roslan; Mohd Shahmi Hakimi Mazlishah; Noorhidayah Mamat; Nor Azlina Abd Aziz; Noor Hashida Hashim; Nuradilla Mohamad-Fauzi (Small Ruminant Research, 2025)

MFCC–ANN model for leak size estimation in pipeline systems - Mohd Fairusham Ghazali; Nor Azinee Said; Muhammad Hanafi Yusop; Erdiwansyah; Muhammad Aminuddin Pi Remli; Rizalman Mamat (Next Research, 2025)

Innovative photothermal membrane distillation: Mitigating temperature polarisation with rice husk biochar - Chia Ming Liew; Mohd Hafiz Puteh; Mohd Hafiz Dzarfan Othman; Roziana Kamaludin; Siti Maryam Jasman; Parvin Asogan; Rendy Muhamad Iqbal; Mustapha Salisu Muhammad; Huda Nurul; Nor Ain Abu Samah; Jerry Heng; Huda Abdullah; et al. (Journal of Environmental Chemical Engineering, 2025)

Physicochemical characterization, lipid-modulating effects, and proteomic insights of Malaysian Sacha Inchi (Plukenetia volubilis L.) seed oil in HepG2 cells - Mariam Fardush; Norsyahida Mohd Fauzi; Ho Wen Yan; Armania Nurdin; Ibrahim Jantan; Nor Azlan bin Nor Muhammad; Siti Nurlisa Hazim; Sarmila Hanim binti Mustafa; Kimberlyn Feguro (Food Bioscience, 2025)

Nanoencapsulation of East Kalimantan propolis with chitosan using modified ionic gelation: Enhanced antioxidant and selective anticancer activity - Putri Hawa Syaifie; Khalish Arsy Al Khairy Siregar; Isna Fadhilah; Alinda Anggraini; Muhammad Miftah Jauhar; Etik Mardliyati; Songchan Puthong; Thitipan Meemongkolkiat; Phanthiwa Khongkarat; Chanpen Chanchao; Muhammad Nor Ichsan; Paula Mariana Kustiawan (Food and Bioproducts Processing, 2025)

Genetic Population of Rusty Jobfish Aphareus Rutilans (Cuvier, 1830), Including a New Sequence Record from South Aceh Waters Indonesia - Sri Riska Rahayu; Abdul Rahman Siregar; Mutia Ramadhaniaty; Nanda Muhammad Razi; Syamsul Rizal; Nur Fadli; Luvi Syafrida Handayani; Martin Wilkes; Mohd Nor Siti-Azizah; Su-fang Niu; Zainal Abidin Muchlisin (Thalassas: An International Journal of Marine Sciences, 2025)

Mechanisms of S-phase arrest and mitochondrial dysfunction in complex III by DHODH inhibitors in tumorigenic TNBC cells - Muhammad Aiman Akmal Shahhiran; Mohamad Fairus Abdul Kadir; Nurshamimi Nor Rashid; Puteri Shafinaz Abdul-Rahman; Shatrah Othman (Histochemistry and Cell Biology, 2025)

DNA barcoding of fish from Singkil peat swamp waters of Aceh Province, Indonesia - Nanda Muhammad Razi; Sri Riska Rahayu; Luvi Syafrida Handayani; Nanda Ulfa Khaira; Muhammad Syukran; Ahmad Sazali A. Sitorus; Cut Tria Aswina; Putri Khairani Amalia Siregar; Muhammad Nasir; Nur Fadli; Martin Wilkes; Mohd Nor Siti-Azizah; et al. (Zoologischer Anzeiger, 2025)

Comprehensive investigation of the smouldering characteristics of hemic peat under varying moisture conditions and the combined influence of wind velocity and direction - Nor Azizah Che Azmi; Ahmad Safuan A Rashid; Nazirah Mohd Apandi; Abd Wahid Rasib; Mohd Nazri Mohd Nasir; Adnan Zainorabidin; Mohamad Sofi Mohamed; Muhammad Amir Mat Shah; Diana Che Lat; Afiqah Ismail (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Oral adjuvanted Vibrio vaccine enhances antibody production and lysozyme activity in the serum and mucus of marine-cultured red hybrid tilapia (Oreochromis sp.) against V. harveyi and V. alginolyticus - Tilusha Manchanayake; Aslah Mohamad; Zahaludin Amir-Danial; Nadirah Abu Nor; Chin Yong-Kit; Muhammad Farhan Nazarudin; Roslindawani Md Nor; Qistina Hasnan; Mohd Zamri-Saad; Mohammad Noor Azmai Amal; Md Yasin Ina-Salwany; Annas Salleh (Fish & Shellfish Immunology, 2025)

Arsenic speciation using HPLC–ICP–MS in white and brown rice and health risk assessment - Raneesha Navaretnam; Ahmad Zaharin Aris; Muhammad Faizan A. Shukor; Mohd Nor Faiz Norrrahim; Victor Feizal Knight; Teen Teen Chin; Noorain Mohd Isa; Ley Juen Looi (Environmental Geochemistry and Health, 2025)

Cytotoxicity of Physalis minima Linn (Solanaceae) fruit against HCT116 and HT29 colorectal cancer cell lines - Wei Lun Ng; Jen Kit Tan; Charles Gnanaraj; Muhammad Dawood Shah; Nurshamimi Nor Rashid; Iskandar Abdullah; Yoong Soon Yong (Natural Product Research, 2025)

High genetic diversity and panmictic population of Malabar trevally (Platycaranx malabaricus) - Nuralif Fakhrullah Mohd Nur; Nur Izzati Zulaidi; Muhammad Hanif Fadzli; Min Pau Tan; Siti Azizah Mohd Nor; Ying Giat Seah; Ahasan Habib; Tun Nurul Aimi Mat Jaafar (Marine Biology, 2025)

Putrescine Detection Via PMMA-Zinc(II) Complex Optical Chemosensor: Meat Spoilage Screening Tool - Muhammad Ameerullah Sahudin; Jian Xiong Tan; Khairun Nasriah Azmi; Nur Afny Suhaimi; Shameer Hisham; Nor Kartini Abu Bakar; Muhammad Nidzhom Zainol Abidin; Khairul Anwar Ishak; Nurul Huda Abd Karim (Journal of Fluorescence, 2025)

Computational Investigation of Hull Vane Effects on Resistance and Propulsive Performance of a Patrol Vessel - Muhammad Irfan Shahmi bin Abdul Ra’uf; Iwan Mustaffa Kamal; Nor Adlina Othman; Yaseen Adnan Ahmed (Journal of Marine Science and Engineering, 2025)
This study investigates the effect of Hull Vane® on the total resistance and propulsion performance of a patrol vessel using computational fluid dynamics (CFD). Utilizing SHIPFLOW software, multiple simulations were conducted to evaluate how Hull Vane® position and angle of attack influence hydrodynamic performance. A patrol vessel hull form the MAXSURF’s library was selected to investigate resistance and propulsive performance. Nine (9) configurations (named Cases A to I) of the Hull Vane® were examined based on variations in longitudinal position and angle of attack. A grid independence study was conducted to determine the optimal mesh configuration. Validation was performed using the Holtrop–Mennen power prediction method and MAXSURF. According to this study, results indicate that Hull Vane® configurations significantly reduce total resistance and delivered power at higher vessel speeds, with the best improvement in resistance occurring in Case C and in propulsion power in Case B. Propulsive efficiency was maximized in Case E. Furthermore, the study also demonstrates the potential of Hull Vane® as a practical retrofit for enhancing naval vessel performance and reducing energy consumption.

Farnesol dehydrogenase from Metisa plana (Lepidoptera: Psychidae): Biochemical characterization, in silico analysis and inhibitors discovery - Anis Nadyra Zifruddin; Ahmad Faris Seman Kamarulzaman; Nor Azlan Nor Muhammad; Kok Wai Lam; Cik Mohd Rizuan Zainal Abidin; Maizom Hassan (Pesticide Biochemistry and Physiology, 2025)

Novel sequential ozonolysis-hydrolysis treatments for microcrystalline cellulose synthesis from oil palm empty fruit bunch - Pavitra Thevi Arnandan; Wan Nor Nadyaini Wan Omar; Zhahidah Husna Hassan; Muhammad Sufri Abd Muhaimin; Danish Akmal Jihat@Ahmad; Makam Mba Michele Raissa; Amnani Shamjuddin; Ken-Lin Chang; Nor Aishah Saidina Amin (Biomass and Bioenergy, 2025)

Disaster risk assessment in Malaysia: current state, challenges, and future directions - Muhammad Wafiy Adli Ramli; Nor Eliza Alias; Zulfaqar Sa’adi; Yusrin Faiz Abdul Wahab; Azimah ABD Rahman (Natural Hazards, 2025)

The effect of chronic microplastic exposure on the growth, biochemical responses, and histological changes of the juvenile sea cucumber Holothuria scabra - Sarah Syazwani Shukhairi; Nurzafirah Mazlan; Nur Nashrah Abd Rahman; Muhammad Nor Afdall Nazahuddin; Amir Syazwan Shawel; Vijay Subbiah Kumar (Environmental Science and Pollution Research, 2025)
Microplastics (MPs) are minuscule plastic particles less than 5 mm in size, originating from the degradation of larger plastic debris. MPs originate from various sources and pose a significant threat to the marine ecosystem. Holothuria scabra is a species of sea cucumber with high commercial value and among the organisms affected by MPs pollution. H. scabra are also crucial in maintaining a clean seabed and recycling nutrients in the ocean ecosystem. Polymethymethacrylate (PMMA), a durable and transparent plastic polymer widely used as a glass alternative in maritime and other industries. This research aimed to investigate the toxicity effects of polymethylmethacrylate-MPs on the well-being of juvenile sea cucumber H. scabra . Over a 60-day treatment period, polymethylmethacrylate MPs were exposed to the juvenile sea cucumber diet at concentrations of 0.6 MPs/g (Treatment 1), 1.2 MPs/g (Treatment 2), and 10 MPs/g (Treatment 3) while a control group which received no MPs exposure to observe changes in their growth, biochemical responses, and histological alteration. The mean weight, weight gain percentage and specific growth rate exhibited significant differences ( p < 0.05) with the control group displaying the highest SGR value of 1.22 ± 0.35%. Mortality was observed in treatment 2 and 3, respectively. A disruption in enzyme activity was also observed across all treatment groups ( p < 0.05). The findings of growth rates and biochemical responses were further supported by histological observation, uncovering injuries and loss of cellular components in respiratory trees and intestines. This study enhances our understanding of the toxicity mechanism associated with PMMA-MPs in deposit feeder organisms.

Endophytes of Zingiberaceae: distribution and bioactivity of their bioactive metabolites - Nor Hazwani Mohd Hasali; Muhammad Shahbaz; Jaya Seelan Sathiya Seelan; Nazirul Azam Ibrahim; Christophe Wiart; Nivaarani Arumugam; Mohammed Abdus Salam; Muneeb M. Musthafa; Suganthi Appalasamy (Archives of Microbiology, 2025)

Genetic and Population Diversity of Temnocephalids Associated with the Invasive Crayfish Cherax quadricarinatus in Malaysia - Norhan N. Azri-Shah; Nor Asma Husna Yusoff; Farizan Abdullah; Ahmad Najmi Ishak; Norainy Mohd Husin; Hin Boo Wee; John Brian Jones; Muhammad Ikhwanuddin; Siti Azizah Mohd Nor; Marina Hassan (Acta Parasitologica, 2025)

Exploring the synergies between natural resources, technological innovation, and fiscal and monetary policies for promoting environmental sustainability in ASEAN countries - Muhammad Azam Khan; Salma Zahir; Nor Salwati Othman; Abdul Majid Awan (Environment, Development and Sustainability, 2025)

Reclaiming Wolffia arrhiza as fish feed for the phytoremediation of aquaculture effluent - Nor Sakinah Mohd Said; Muhammad Zahin Zakaria; Norsyasmin Izzati Samsuddin; Nur Aina'a Zafirah Barom; Navieen AL. M. Murugiah; Siti Rozaimah Sheikh Abdullah (Journal of Environmental Management, 2025)

Malaria parasite detection in Red Blood Cells with rouleaux formation morphology using YOLOv9 - Fatima Abdullahi Muhammad; Rubita Sudirman; Nor Aini Zakaria (Tissue and Cell, 2025)

Tracking the tropical aquatic dragon: environmental DNA (eDNA) detection for monitoring the endangered Asian arowana, Scleropages formosus (Müller and Schlegel, 1840) - Norli Fauzani Mohd Abu Hassan Alshari; Muhammad Hanif Iryani Adnan; Danial Hariz Zainal Abidin; Siti Zafirah Ghazali; Min Pau Tan; Noor Adelyna Mohammed Akib; Sébastien Lavoué; Siti Azizah Mohd Nor (Hydrobiologia, 2025)

Coral diversity and abundance patterns at the West Coast of Sabah: a case study of Kota Kinabalu coral reefs - Khodzori Fikri Akmal; Nor’ashikin Aslam Zuhairi; Zepri Abdul Muhaimin; Zarinah Waheed; Muhammad Ali Syed Hussein; Gan Sze Hoon; Yee Tong Kiu; Khairul Hisham Hariz; Mazni Muhammad Addin; Siti Nur Hazwani Oslan (Community Ecology, 2025)

Impact of Storm Pabuk on a Monsoon Coral Beach: Bidong Island, Terengganu (Malaysia) - Siti Nur Hanani Zainuddin; Che Din Mohd Safuan; Junainah Zakaria; Cherdvong Saengsupavanich; Muhammad Zahir Ramli; Azizi Ali; Zainudin Bachok; Fatihah Shariful; Alya Syakirah Tajul Ariffin; Idham Khalil; Aidy M. Muslim; Hasrizal Shaari; et al. (Marine Geology, 2025)

Transcriptomic analyses reveal the upregulation of the fatty acids metabolism genes in Thalassiosira weissflogii during low optimal phosphate concentration - Muhammad Faiz Zakaria; Ahmad Hanafi Ahmad Kamal; Nor Afiqah-Aleng; Mohd Effendy Abd Wahid; Ghows Azzam; Tomoyo Katayama; Kazutaka Takahashi; Kamariah Bakar; Hock Seng Tan; Malinna Jusoh (Aquaculture, 2025)

De novo transcriptome analysis and gene expression profiling of Conticribra weissflogii during low salinity reveals regulation of fatty acid biosynthesis genes - Muhammad Faiz Zakaria; Ahmad Hanafi Ahmad Kamal; Noor Amanina Awang; Nor Afiqah-Aleng; Kamariah Bakar; Noorul Darlina Edlin Abd Rahim; Hock-Seng Tan; Mohd Effendy Abd Wahid; Ghows Azzam; Malinna Jusoh (Journal of Applied Phycology, 2025)

Elucidation of synbiotic diet comprising of Lactobacillus plantarum L20 and Sargassum polycystum on gastrointestinal microbiota, tissue structures and AHPND associated dysbiosis susceptibility in black tiger shrimp (Penaeus monodon) - Yong Kit Chin; Mohamad Azzam-Sayuti; Aslah Mohamad; Wan Omar Haifa-Haryani; Mohd Ihsanuddin Ahmad; Muhammad Farhan Nazarudin; Nur Shidaa Mohd Ali; Md Yasin Ida-Muryany; Murni Marlina Abd Karim; Salleh Annas; Mohd Nor Norhariani; Mohammad Noor Azmai Amal; et al. (Aquaculture, 2025)

Assessing the concentration, distribution and characteristics of suspended microplastics in the Malaysian indoor environment - M. Dewika; Kalaimani Markandan; Shalini Nagaratnam; N. Ahmad Irfan; Muhammad Amirul Aizat Mohd Abdah; J. Nor Ruwaida; Y.Y. Sara; Mohammad Khalid (Science of The Total Environment, 2025)

Phytotreatment of tofu effluent using water lettuce (Pistia stratiotes) and potential of biogas production from resultant biomass - Setyo Budi Kurniawan; Muhammad Fauzul Imron; Rikky Ramadhan Mustofa; Dhuroton Najiya; Nor Sakinah Mohd Said; Junaidah Buhari; Hajjar Hartini Wan Jusoh; Azimah Ismail (Journal of Water Process Engineering, 2025)

Evaluation of Microplastics Ingested by Sea Cucumber Holothuria Scabra from Pulau Jambongan, Sabah - Sarah Syazwani Shukhairi; Nurzafirah Mazlan; Vijay Kumar Subbiah; Nur Nashrah Abd Rahman; Muhammad Nor Afdall Nazahuddin; Amir Syazwan Shawel; Audrey Daning Tuzan; Sitti Raehanah Muhammad Shaleh; Norfazreena Mohd Faudzi; Rossita Shapawi; Muhammad Dawood Shah; Tze Young Thung (Bulletin of Environmental Contamination and Toxicology, 2025)

In silico prediction of effector proteins in oil palm pest, Metisa plana - Mohamad Ariff Mohamad Yussoff; Maizom Hassan; Norfarhan Mohd-Assaad; Nurul Wahida Othman; Suhaila Sulaiman; Cik Mohd Rizuan Zainal Abidin; Nor Azlan Nor Muhammad (Journal of Asia-Pacific Entomology, 2024)

Identification and mechanism determination of the efflux pump subunit amrB gene mutations linked to gentamicin susceptibility in clinical Burkholderia pseudomallei from Malaysian Borneo - Ainulkhir Hussin; Sheila Nathan; Muhammad Ashraf Shahidan; Mohd Yusof Nor Rahim; Mohamad Yusof Zainun; Nurul Aiman Nafisah Khairuddin; Nazlina Ibrahim (Molecular Genetics and Genomics, 2024)

Improving green hydrogen production: Microwave-assisted synthesis of diverse Ni-based nanocatalysts on Al2O3 for thermochemical water splitting - Salma Samidin; Wan Nor Roslam Wan Isahak; Khairul Naim Ahmad; N. Asikin Mijan; Muhammad Rahimi Yusop; Alinda Samsuri; G. Abdulkareem-Alsultan; Mohd Ambar Yarmo (Fuel, 2024)

Innovative solutions for the removal of emerging microplastics from water by utilizing advanced techniques - Noornama; Muhammad Nidzhom Zainol Abidin; Nor Kartini Abu Bakar; Nur Awanis Hashim (Marine Pollution Bulletin, 2024)

In-depth analysis of ambient air pollution changes due to the COVID-19 pandemic in the Asian Monsoon region - Mohd Talib Latif; Noorain Purhanudin; Nur Zulaikha Mohd Afandi; Maria Obiminda L. Cambaliza; Nor Diana Abdul Halim; Nor Syamimi Sufiera Limi Hawari; To Thi Hien; Ohnmar May Tin Hlaing; Warnakulasuriya Roshani Loreta Hiranthi Jansz; Muhammad Fahim Khokhar; Puji Lestari; Shih-Chun Candice Lung; et al. (Science of The Total Environment, 2024)

Storm surge induced by 2019 Tropical Storm Pabuk and impact on the shoreline in Kuala Nerus Terengganu, east coast of Peninsular Malaysia - Wan Amrul Jaahiz Abd Razak; Muhammad Zahir Ramli; Nor Bakhiah Baharim; Syazana Md Shubri; Junainah Zakaria; Muhammad Fadhli Harris; Azizi Ali; Effi Helmy Ariffin (Regional Studies in Marine Science, 2024)

In vivo assessment of Lactobacillus plantarum strains in black tiger shrimp (Penaeus monodon): implications for growth performance, probiotic-pathogen interaction, and defense against AHPND infection - Yong Kit Chin; Wan Omar Haifa-Haryani; Muhammad Farhan Nazarudin; Mohd Ihsanuddin Ahmad; Mohamad Azzam-Sayuti; Nur Shidda Mohd Ali; Mohamad Syazwan Ngalimat; Aslah Mohamad; Md Yasin Ida-Muryany; Murni Karim; Annas Salleh; Mohd Nor Norhariani; et al. (Aquaculture International, 2024)

Enhancing the CO2 adsorption with dual functionalized coconut shell-hydrochar using Chlorella microalgae and metal oxide: Synthesis, physicochemical properties & mechanism evaluations - Nuradila Zahirah Mohd Azmi; Archina Buthiyappan; Muhammad Fazly Abdul Patah; Nor Adilla Rashidi; Abdul Aziz Abdul Raman (Journal of Cleaner Production, 2024)

Characterization of the future northeast monsoon rainfall based on the clustered climate zone under CMIP6 in Peninsular Malaysia - Zulfaqar Sa'adi; Nor Eliza Alias; Zulkifli Yusop; Mohammed Magdy Hamed; Prabhakar Shukla; Mohamad Rajab Houmsi; Nur Athirah Mohamad; Mohammed Sanusi Shiru; Nurzalikha Sa'adi; Mohd Khairul Idlan Muhammad; Zafar Iqbal; Umer Jeelanie Banday (Atmospheric Research, 2024)

Opportunity for genome engineering to enhance phosphate homeostasis in crops - Siti Nor Akmar Abdullah; Norazrin Ariffin; Muhammad Asyraf Md Hatta; Nurashikin Kemat (Physiology and Molecular Biology of Plants, 2024)

Forward osmosis as a contemporary treatment solution for mitigating radionuclide pollution in water bodies - Muhammad ‘Adli Nor Azman; Pei Sean Goh; Ahmad Fauzi Ismail; Khairulnadzmi Jamaluddin; Keng Yinn Wong; Ahmad Syazwan Sahril (Journal of Environmental Chemical Engineering, 2024)

Employing gridded-based dataset for heatwave assessment and future projection in Peninsular Malaysia - Zulfaqar Sa’adi; Mohammed Magdy Hamed; Mohd Khairul Idlan Muhammad; Ming Fai Chow; Nur Athirah Mohamad; Mohd Hadi Akbar Basri; Mohamad Faizal Ahmad; Nurzalikha Sa’adi; Nor Eliza Alias; Zulkifli Yusop; Mohamad Rajab Houmsi; Prabhakar Shukla; et al. (Theoretical and Applied Climatology, 2024)

Seasonal Variability On Cross-shore Profile in Meso-tidal Settings Due to Lunar Cycle Effects in Kuala Terengganu Coast - Muhammad Fadhli Harris; Muhammad Izuan Nadzri; Ku Mohd Kalkausar Ku Yusof; Wan Amrul Jaahiz Abd Razak; Mohamad Hakim Mohd Shukri; Nor Bakhiah Baharim; Azizi Ali; Effi Helmy Ariffin (Thalassas: An International Journal of Marine Sciences, 2024)

Growth Patterns, Condition Factor, and Population Dynamics of Snapper Lutjanus bengalensis and Lutjanus lutjanus (Pisces: Lutjanidae) Harvested from Aceh Waters Indonesia - Sri Riska Rahayu; Syamsul Rizal; Nur Fadli; Ilham Raza; Muhammad Isran Lazuardi; Luvi Syafrida Handayani; Nanda Muhammad Razi; Martin Wilkes; Mohd Nor Siti-Azizah; Zainal A. Muchlisin (Thalassas: An International Journal of Marine Sciences, 2024)

Impact of climate change awareness on household attitude toward food waste reduction - Chimeziem Elijah Nwankwo-Ojionu; Nor Azura Adzharuddin; Moniza Waheed; Azlina Mohd Khir; Muhammad Mansur Abdulwakil; Chioma Mercy Chimeziem Ehiemere (Journal of Environmental Studies and Sciences, 2024)

A control rod worth prediction using Adaptive Neuro-Fuzzy Inference System for Pre-Calibration Method at TRIGA PUSPATI Reactor - Teh Zhi Hui; Nur Syazwani Mohd Ali; Mohd Sabri Minhat; Jasman Zainal; Muhammad Arif Sazali; Muhammad Syahir Sarkawi; Khairulnadzmi Jamaluddin; Nor Afifah Basri; Mohsin Mohd Sies; Nahrul Khair Alang Md Rashid (Annals of Nuclear Energy, 2024)

Factors determining water stress: do environmental distress, energy consumption and industrialization matter? - Muhammad Azam Khan; Ijaz Uddin; Nor Salwati Othman (Environment, Development and Sustainability, 2024)

Sciscionella sediminilitoris sp. nov., a Marine Actinomycete Isolated from Cape Rochado, Malaysia, and the Emendations to the Description of the Genus Sciscionella - Wee Fei Aaron Teo; Kavimalar Devaraj; Muhammad Nuruddin Mohd Nor; Wen-Jun Li; Geok Yuan Annie Tan (Current Microbiology, 2024)

Insights of the Rhynchophorus ferrugineus chemosensory system towards controlling its palm infestation problem: Progress from Omics research and technologies - Rajeswari Kalepu; Maizom Hassan; Norfarhan Mohd Assa’ad; Azzmer Azzar Abdul Hamid; Nor Azlan Nor Muhammad (International Journal of Tropical Insect Science, 2024)

Molybdenum oxide-based catalyst towards better hydrogen production: effects of isothermal carburization - Mohd Nor Latif; Nur Syakirah Abdul Rahim; Salma Samidin; Siti Hasnawati Jamal; Muhammad Rahimi Yusop; Wan Nor Roslam Wan Isahak; Alinda Samsuri (Environmental Science and Pollution Research, 2024)

Utilizing a Low-Cost Air Quality Sensor: Assessing Air Pollutant Concentrations and Risks Using Low-Cost Sensors in Selangor, Malaysia - Zaki Khaslan; Mohd Shahrul Mohd Nadzir; Hamimatunnisa Johar; Zhang Siqi; Nor Azura Sulong; Faizal Mohamed; Shubhankar Majumdar; Fatin Nur Afiqah Suris; Nor Syamimi Sufiera Limi Hawari; Jintu Borah; Maggie Ooi Chel Gee; Muhammad Ikram A. Wahab; et al. (Water, Air, & Soil Pollution, 2024)

Biochemical and in silico structural characterization of a cold-active arginase from the psychrophilic yeast, Glaciozyma antarctica PI12 - Nik Yusnoraini Yusof; Doris Huai Xia Quay; Shazilah Kamaruddin; Mohd Anuar Jonet; Rosli Md Illias; Nor Muhammad Mahadi; Mohd Firdaus-Raih; Farah Diba Abu Bakar; Abdul Munir Abdul Murad (Extremophiles, 2024)

CHIRPS rainfall product application for analyzing rainfall concentration and seasonality in Johor river basin, Malaysia - Zulfaqar Sa’adi; Nor Eliza Alias; Zulkifli Yusop; Muhammad Wafiy Adli Ramli; Mohd Khairul Idlan Muhammad (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Evaluation of the microplastics in bivalves and water column at Pantai Teluk Likas, North Borneo, Malaysia - Nur Nashrah Abd Rahman; Nurzafirah Mazlan; Sarah Syazwani Shukhairi; Muhammad Nor Afdall Nazahuddin; Amir Syazwan Shawel; Haniza Harun; Afaf Baktir (Environmental Science and Pollution Research, 2024)

Adopting Marine Spatial Planning (MSP) using coral health assessment as indicator: A case study in Pulau Redang Marine Park, Malaysia - Farhana Razak; Wei Yien Lua; Nor Hafzan Abd Rasid; Nazli Aziz; Izarenah Md Repin; Xiong-Zhi Xue; Abdul Rahman Muhammad Ashraf; Zainudin Bachok; Aminudin Afiq-Firdaus; Wan Izatul Asma Wan Talaat; Abdul Rahman Abdul Latip; Che Din Mohd Safuan (Ocean & Coastal Management, 2024)

Application of relative importance metrics for CMIP6 models selection in projecting basin-scale rainfall over Johor River basin, Malaysia - Zulfaqar Sa'adi; Nor Eliza Alias; Zulkifli Yusop; Zafar Iqbal; Mohamad Rajab Houmsi; Lama Nasrallah Houmsi; Muhammad Wafiy Adli Ramli; Mohd Khairul Idlan Muhammad (Science of The Total Environment, 2024)

Modified carbon paste electrode with choline proline in enhancing the performance of water electrolysis system for hydrogen production - Muhammad Usman; Fakrul Shahril Ezanie Zulkefli; Mohd Dzul Hakim Wirzal; Shafiq M. Hizam; Aliya Nurzafira Nor Zaidi; Muhammad Syaamil Saad (Fuel, 2024)

Pediococcus pentosaceus LAB6- and Lactiplantibacillus plantarum LAB12-Derived Cell Free Supernatant Inhibited RhoA Activation and Reduced Amyloid-Β In Vitro - Ramli Muhammad Zaki; Kalavathy Ramasamy; Nor Amalina Ahmad Alwi; Rosmadi Mohd Yusoff; Siong Meng Lim (Probiotics and Antimicrobial Proteins, 2024)

Current progress on the computational methods for prediction of host-pathogen protein-protein interaction in the Ganoderma boninense-oil palm pathosystem - Mohamad Hazwan Fikri Khairi; Nor Azlan Nor Muhammad; Hamidun Bunawan; Kauthar Mohd Daud; Suhaila Sulaiman; Zeti-Azura Mohamed-Hussein; Mui-Yun Wong; Ahmad Bazli Ramzi (Physiological and Molecular Plant Pathology, 2024)

Ambassis octava, a new glass-perchlet species (Teleostei: Ovalentaria: Ambassidae) from Peninsular Malaysia - Siti Zafirah Ghazali; Sébastien Lavoué; Siti Azizah Mohd Nor; Abdullah Halim Muhammad-Rasul; Min Pau Tan (Ichthyological Research, 2024)

Alkaline earth metal modified nickel nanoparticles supported on exfoliated g-C3N4 for atmospheric CO2 methanation - Khairul Naim Ahmad; Salma Samidin; Masli Irwan Rosli; Muhammad Rahimi Yusop; Mohammad B. Kassim; Bamidele Victor Ayodele; Mohd Ambar Yarmo; Wan Nor Roslam Wan Isahak (Journal of Environmental Chemical Engineering, 2023)

In situ stannous reagent generator (SRG): An alternative hexavalent chromium treatment technology in drinking water industry - Mohd Hushni Mohd Yusof; Shamsul Sarip; Abdul Yasser Abd Fatah; Hazilah Mad Kaidi; Firdaus Muhammad-Sukki; Nor Fazilah Mohd Hashim (Journal of Water Process Engineering, 2023)

The effects of cultivation type and maturity stage on arsenic species concentration and carrageenan content in Kappaphycus spp. from Semporna, Sabah - Ghanthimathi Subramaniam; Noumie Surugau; Nor Azwady Abd Aziz; Radhiah Shukri; Kharidah Muhammad (Journal of Applied Phycology, 2023)

Oilseed meals into foods: an approach for the valorization of oilseed by-products - Gita Addelia Nevara; Shafa’atu Giwa Ibrahim; Sharifah Kharidah Syed Muhammad; Norhasnida Zawawi; Nor Afizah Mustapha; Roselina Karim (Critical Reviews in Food Science and Nutrition, 2023)

Application of CHIRPS dataset in the selection of rain-based indices for drought assessments in Johor River Basin, Malaysia - Zulfaqar Sa'adi; Zulkifli Yusop; Nor Eliza Alias; Mohammed Sanusi Shiru; Mohd Khairul Idlan Muhammad; Muhammad Wafiy Adli Ramli (Science of The Total Environment, 2023)

Synthesis of ethyl levulinate over sulfonated lignin-based carbon catalyst as a fuel additive to biodiesel-diesel blends towards engine emissions - Abdull Hafidz Hassan; Muzakkir Mohammad Zainol; Muhammad Alif Samion; Muhammad A`qil Azlan; Mohd Asmadi; Ahmad Rafizan Mohamad Daud; Idris Saad; Nur Aina Najwa Mohd Nor Azman (Journal of Cleaner Production, 2023)

Adaptation of coastal defence structure as a mechanism to alleviate coastal erosion in monsoon dominated coast of Peninsular Malaysia - Wan Shiao Dong; Effi Helmy Ariffin; Cherdvong Saengsupavanich; Muhammad Aizat Mohd Rashid; Mohamad Hakim Mohd Shukri; Muhammad Zahir Ramli; Mohd Fuad Miskon; Muhammad Hafeez Jeofry; Kamaruzzaman Yunus; Nor Hisham M. Ghazali; Md Nasir Md Noh (Journal of Environmental Management, 2023)

High prevalence of multiple antibiotic resistance in fermented food-associated lactic acid bacteria in Malaysia - Yuli Haryani; Nadrah Abdul Halid; Goh Sur Guat; Mahmud Ab Rashid Nor-Khaizura; Muhammad Asyraf Md Hatta; Suriana Sabri; Son Radu; Hanan Hasan (Food Control, 2023)

Advances in production & activation of marine macroalgae-derived biochar catalyst for sustainable biodiesel production - Muhammad Zubair Yameen; Hamad AlMohamadi; Salman Raza Naqvi; Tayyaba Noor; Wei-Hsin Chen; Nor Aishah Saidina Amin (Fuel, 2023)

Implementation of the energy efficiency existing ship index and carbon intensity indicator on domestic ship for marine environmental protection - Lai Fatt Chuah; Kasypi Mokhtar; Siti Marsila Mhd Ruslan; Anuar Abu Bakar; Mohd Azhafiz Abdullah; Nor Hasni Osman; Awais Bokhari; Muhammad Mubashir; Pau Loke Show (Environmental Research, 2023)

Understanding the quality and potential of groundwater for human purposes and peat fire disaster mitigation - Nur Islami; Mitri Irianti; Azhar Azhar; Muhammad Nor; Fakhruddin Fakhruddin (Arabian Journal of Geosciences, 2023)

Aerobic granular sludge development using diatomite for low-strength wastewater treatment - Hazlami Fikri Basri; Aznah Nor Anuar; Mohd Hakim Ab Halim; Muhammad Ali Yuzir; Khalida Muda; Armstrong Ighodalo Omoregie; Mohamed Zuhaili Mohamed Najib (Environmental Monitoring and Assessment, 2023)

Recent progress in catalytic deoxygenation of biomass pyrolysis oil using microporous zeolites for green fuels production - Salman Raza Naqvi; Asif Hussain Khoja; Imtiaz Ali; Muhammad Naqvi; Tayyaba Noor; Awais Ahmad; Rafael Luque; Nor Aishah Saidina Amin (Fuel, 2023)

Centella asiatica (L.) Urb. Extract ameliorates branched-chain amino acid (BCAA) metabolism in acute reserpine-induced stress zebrafish model via 1H Nuclear Magnetic Resonance (NMR)-based metabolomics approach - Fauziahanim Zakaria; Muhammad Tayyab Akhtar; Wan Ibrahim Wan Norhamidah; Abu Bakar Noraini; Azira Muhamad; Shamarina Shohaimi; Maulidiani; Hafandi Ahmad; Intan Safinar Ismail; Nor Hadiani Ismail; Khozirah Shaari (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

The mechanism for bond behavior of concrete with two-staged treated rubber filled steel tube - Abu Bakar Nabilah; Nor Azizi Safiee; Noor Azline Mohd Nasir; Muhammad Fakhrul Radzi Abdul Rahman; Abdulrahman Khaleel Midhin (European Journal of Environmental and Civil Engineering, 2023)

Fusarium falciforme and F. oxysporum causing postharvest fruit rot of watermelon (Citrullus lanatus) in Malaysia: A first report - Jagaathiswary Balasubramaniam; Ka Sheng Goh; Safia Fazariah Sani; Muhammad Waqar Alam; Nor Azliza Ismail; Mark L. Gleason; Hafizi Rosli (Crop Protection, 2023)

Corrigendum to “Priorities to inform research on marine plastic pollution in Southeast Asia” [Sci. Total Environ. volume 841 (2022) Article 156704] - Lucy C.M. Omeyer; Emily M. Duncan; Kornrawee Aiemsomboon; Nicola Beaumont; Sujaree Bureekul; Bin Cao; Luis R. Carrasco; Suchana Chavanich; James R. Clark; Muhammad R. Cordova; Fay Couceiro; Simon M. Cragg; et al. (Science of The Total Environment, 2023)

Mapping of marine lobster research: A global outlook - Mohamad Nor Azra; Mok Wen Jye; Hien Van Doan; Ivar Zekker; Muhammad Fuad Abdullah; Zulkiflee Abd Latif; Mohd Iqbal Mohd Noor (Frontiers in Marine Science, 2022)
This study examined research and development of the commercially important marine lobster, in terms of descriptive metadata and scientometric analysis. We consider a collection of over 9,578 related articles to assess literature patterns and research development trends related to marine lobsters as a topic. Web of Science Core Collection was used to identify, collate, and generate publication trends, a list prominent authors and affiliations involved, countries that actively participated, and the co-citation analysis of the references as well as impactful articles and keywords. There were 149 different countries or states that had relevant publications on lobster research. We found an increase in the number of publications over time, with the USA having the most number of publications, followed by Australia and Canada. A total of 17,782 authors were involved in the field of lobster studies. Canadian researchers had the highest citation count for marine lobster research. Surprisingly, the most impactful keyword was crayfish, followed by neuron and amino acid sequence. Our study identifies the multidisciplinary nature in marine lobster research, which includes fields such as neuroscience and developmental genetics. We find that lobster scientific publications increasingly center on the broader coverage areas of science such as taxonomy and basic biology.

Nutritional compositions, pathogenic microorganisms and heavy metal concentration in green turtle eggs (Chelonia mydas) from Terengganu and Sabah, Malaysia - Nor Hashikin Katni; Amirul Faiz Mohd Azmi; Maizah Mohd Abdullah; Mohd Uzair Rusli; Zunita Zakaria; Tengku Rinalfi Putra Tengku Azizan; Azlan Che’ Amat; Mohd Zamri Saad; Ina Salwany Md. Yasin; Muhammad Farhan Nazarudin; Hasliza Abu Hassim (Frontiers in Marine Science, 2022)
A total of 60 green turtle eggs were obtained from sampling sites in Terengganu and Sabah, Malaysia. Isolation and identification of bacteria from these eggs resulted in 12 genera of Gram-negative bacteria with 12 different species. The most frequently isolated bacteria were Salmonella (30.9%) and Proteus (23.7%). The rest of the microorganisms were Aeromonas, Escherichia, Citrobacter, Enterobacter, Klebsiella, Morganella, Pseudomonas, Shigella, Serratia and Photobacterium. A slight difference in total crude protein content was recorded in the samples from Terengganu and Sabah, at 16.3% Dry matter (DM) and 15.8% DM, respectively. Meanwhile, the crude fat content found in the samples from Terengganu was 9.88% DM and 7.79% DM from Sabah. In this study, α-linolenic acid, C18:3 n-3 (Terengganu: 16.87% DM) and linoleic acid, C18:2 n-6 (Sabah: 15.19% DM) were the most prevalent fatty acids in both samples. The green turtle egg samples from Terengganu showed higher value of total saturated fatty acid, total C18:3 n-3 and C18:2 n-6 and total polyunsaturated fatty acids as compared to green turtle eggs from Sabah. The results also revealed that majority of the essential amino acids (EAA) recorded in samples from both sampling sites was lysine (9.67% DM), with higher value recorded in green turtle egg from Terengganu. However, there were no significant differences ( p >0.05) in the nutritional compositions, fatty acid contents and amino acid compositions of the samples between the two sampling sites. Meanwhile, statistical analysis showed significant differences in heavy metal concentrations between the two sampling sites for all the six heavy metals detected in this study (Hg, Cd, Pb, Mn, Zn and Cu). The ranking of heavy metals concentration in turtle eggs from both sampling sites, in decreasing order is as follows: Zn > Cu > Mn > Pb > Cd > Hg. Overall, these results reveal the contents and contaminations of a green turtle egg, which may raise concern on public health risks. Findings from this study will also be beneficial for the future conservation of green turtle population when the consumption of their eggs should be stopped.

Isolation and characterization of acid-tolerant Stichococcus-like Microalga (Tetratostichococcus sp. P1) from a tropical peatland in Malaysia - Eri Sahabudin; Jinwoong Lee; Ryo Asada; Ezzah Atikah Marsid; Nurtasbiyah Yusof; Nurul Syazwani Ahmad Sabri; Hani Susanti; Muhamad Ali Muhammad Yuzir; Fazrena Nadia Md Akhir; Nor’azizi Othman; Zuriati Zakaria; Kengo Suzuki; et al. (Journal of Applied Phycology, 2022)

Correction to: Molecular DNA-based spatial mapping technique predicting diversity and distribution of otters (Lutrinae) in Peninsular Malaysia using non-invasive fecal samples - Pazil Abdul-Patah; Hiroshi Sasaki; Takeshi Sekiguchi; Md Nor Shukor; Nur Syafika Mohd-Yusof; Muhammad Abu Bakar Abdul-Latiff; Badrul Munir Md-Zain (Mammal Research, 2022)

Can heat shock protein 70 (HSP70) serve as biomarkers in Antarctica for future ocean acidification, warming and salinity stress? - Nur Athirah Yusof; Makdi Masnoddin; Jennifer Charles; Ying Qing Thien; Farhan Nazaie Nasib; Clemente Michael Vui Ling Wong; Abdul Munir Abdul Murad; Nor Muhammad Mahadi; Izwan Bharudin (Polar Biology, 2022)
The Antarctic Peninsula is one of the fastest-warming places on Earth. Elevated sea water temperatures cause glacier and sea ice melting. When icebergs melt into the ocean, it “freshens” the saltwater around them, reducing its salinity. The oceans absorb excess anthropogenic carbon dioxide (CO 2 ) causing decline in ocean pH, a process known as ocean acidification. Many marine organisms are specifically affected by ocean warming, freshening and acidification. Due to the sensitivity of Antarctica to global warming, using biomarkers is the best way for scientists to predict more accurately future climate change and provide useful information or ecological risk assessments. The 70-kilodalton (kDa) heat shock protein (HSP70) chaperones have been used as biomarkers of stress in temperate and tropical environments. The induction of the HSP70 genes ( Hsp70 ) that alter intracellular proteins in living organisms is a signal triggered by environmental temperature changes. Induction of Hsp70 has been observed both in eukaryotes and in prokaryotes as response to environmental stressors including increased and decreased temperature, salinity, pH and the combined effects of changes in temperature, acidification and salinity stress. Generally, HSP70s play critical roles in numerous complex processes of metabolism; their synthesis can usually be increased or decreased during stressful conditions. However, there is a question as to whether HSP70s may serve as excellent biomarkers in the Antarctic considering the long residence time of Antarctic organisms in a cold polar environment which appears to have greatly modified the response of heat responding transcriptional systems. This review provides insight into the vital roles of HSP70 that make them ideal candidates as biomarkers for identifying resistance and resilience in response to abiotic stressors associated with climate change, which are the effects of ocean warming, freshening and acidification in Antarctic organisms.

Cellulosic fiber nanocomposite application review with zinc oxide antimicrobial agent nanoparticle: an opt for COVID-19 purpose - Amizon Azizan; Aisyah Afiqah Samsudin; Minhalina Batrisyia Shamshul Baharin; Muhammad Harith Dzulkiflee; Nor Roslina Rosli; Noor Fitrah Abu Bakar; Muhammad Adlim (Environmental Science and Pollution Research, 2022)

Chromosome identification in oil palm (Elaeis guineensis) using in situ hybridization with massive pools of single copy oligonucleotides and transferability across Arecaceae species - Noorhariza Mohd Zaki; Trude Schwarzacher; Rajinder Singh; Maria Madon; Corey Wischmeyer; Nordiana Hanim Mohd Nor; Muhammad Azwan Zulkifli; J. S. Heslop-Harrison (Chromosome Research, 2021)

Carbonated ground granulated blast furnace slag stabilising brown kaolin - Ahmed Mohammed Awad Mohammed; Nor Zurairahetty Mohd Yunus; Muhammad Azril Hezmi; Ahmad Safuan A. Rashid; Suksun Horpibulsuk (Environmental Science and Pollution Research, 2021)

Recent development in ecdysone receptor of crustaceans: current knowledge and future applications in crustacean aquaculture - Muhammad‐Redha Abdullah‐Zawawi; Nor Afiqah‐Aleng; Mhd Ikhwanuddin; Yeong Yik Sung; Siriporn Tola; Hanafiah Fazhan; Khor Waiho (Reviews in Aquaculture, 2021)
Ecdysone receptor (EcR) is the primary regulator of the ecdysteroid signalling pathway, a critical pathway that directly links to moulting. In addition, EcR also regulates growth, development, reproduction and regeneration in crustaceans. However, there remains a huge gap of knowledge between the detailed structure and functional role(s) of crustacean EcR compared to that of insects. Motif and phylogenetic analyses of publicly available crustacean EcR proteins revealed the evolutionary relationship of EcR in this subphylum and highlighted its conserved characteristics among crustaceans. The role of EcR in the regulation of essential physiological processes in crustaceans including moulting, chitin synthesis, general growth and development, gonadal and maturation, and limb regeneration was discussed based on the available literature. This essential moult‐related nuclear receptor could serve as a useful molecular indicator of moulting and gonadal maturation, as a potential target for pesticide production against parasitic crustacean species in the aquaculture industry, as well as valuable bioindicators of environmental stressors.

Genome-wide molecular characterization of Phosphate Transporter 1 and Phosphate Starvation Response gene families in Elaeis guineensis Jacq. and their transcriptional response under different levels of phosphate starvation - Muhammad Luqman Hamzah; Siti Nor Akmar Abdullah; Azzreena Mohamad Azzeme (Acta Physiologiae Plantarum, 2021)

Proteasomal degradation of p130 facilitate cell cycle deregulation and impairment of cellular differentiation in high-risk Human Papillomavirus 16 and 18 E7 transfected cells - Sivasangkary Gandhi; Nurshamimi Nor Rashid; Muhammad Fazril Mohamad Razif; Shatrah Othman (Molecular Biology Reports, 2021)

Polymerase chain reaction cycle threshold value as prerequisite for reporting of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) detection - Hafizuddin Awang; Fathul Hakim Hamzah; Mohd Hanief Ahmad; Muhammad Faris Mahmood; Azmani Wahab; Kasemani Embong; Nor Azimi Yunus (Infectious Diseases, 2021)

Synthesis, β-glucuronidase inhibition and molecular docking studies of cyano-substituted bisindole hydrazone hybrids - Obaidurahman Abid; Syahrul Imran; Muhammad Taha; Nor Hadiani Ismail; Waqas Jamil; Syed Muhammad Kashif; Khalid Mohammed Khan; Juliana Yusoff (Molecular Diversity, 2021)

A case–control study of determinants for COVID-19 infection based on contact tracing in Dungun district, Terengganu state of Malaysia - Hafizuddin Awang; Effah Leiylena Yaacob; Sharifah Nadira Syed Aluawi; Muhammad Faris Mahmood; Fathul Hakim Hamzah; Azmani Wahab; Norafidah Abdul Rashid; Rosmaliza Razali; Goh Soo Ning; Kasemani Embong; Nor Azimi Yunus (Infectious Diseases, 2021)

Correction to: Ground improvement and its role in carbon dioxide reduction: a review - Ahmed Mohammed Awad Mohammed; Nor Zurairahetty Mohd Yunus; Muhammad Azril Hezmi; Dayang Zulaika Abang Hasbollah; Ahmad Safuan A Rashid (Environmental Science and Pollution Research, 2021)

Ground improvement and its role in carbon dioxide reduction: a review - Mohammed Awad Mohammed; Nor Zurairahetty Mohd Yunus; Muhammad Azril Hezmi; Dayang Zulaika Abang Hasbollah; Ahmad Safuan A Rashid (Environmental Science and Pollution Research, 2021)

Effect of Water Temperature on Survival, Growth and Molting Cycle During Early Crablet Instar of Mud Crab, Scylla paramamosain (Estampador, 1950) - Muhammad Nur Syafaat; Syahnon Mohammad; Mohamad Nor Azra; Hongyu Ma; Ambok Bolong Abol-Munafi; Mhd Ikhwanuddin (Thalassas: An International Journal of Marine Sciences, 2020)

Telomerase reverse transcriptase downregulation by RNA interference modulates endoplasmic reticulum stress and mitochondrial energy production - Muhammad Zuhair Mohd Zain; Nor Hayati Ismail; Nadhirah Ahmad; Sarina Sulong; Saiful Anuar Karsani; Nazia Abdul Majid (Molecular Biology Reports, 2020)

Molecular DNA-based spatial mapping technique predicting diversity and distribution of otters (Lutrinae) in Peninsular Malaysia using non-invasive fecal samples - Pazil Abdul-Patah; Hiroshi Sasaki; Takeshi Sekiguchi; Md Nor Shukor; Nur Syafika Mohd-Yusof; Muhammad Abu Bakar Abdul-Latiff; Badrul Munir Md-Zain (Mammal Research, 2020)

Application of geoelectrical resistivity method for the assessment of shallow aquifer quality in landfill areas - Nur Islami; Mitri Irianti; Fakhruddin Fakhruddin; Azhar Azhar; Muhammad Nor (Environmental Monitoring and Assessment, 2020)

Detecting Rainfall Trend and Development of Future Intensity Duration Frequency (IDF) Curve for the State of Kelantan - Muhammad Saiful Adham Shukor; Zulkifli Yusop; Fadhillah Yusof; Zulfaqar Sa’adi; Nor Eliza Alias (Water Resources Management, 2020)

Evaluating the toxicity of polyurethane during marine clay stabilisation - Samaila Saleh; Kamarudin Ahmad; Nor Zurairahetty Mohd Yunus; Muhammad Azril Hezmi (Environmental Science and Pollution Research, 2020)

Assessment of denitrification potential for coastal and inland sites using groundwater and soil analysis: the multivariate approach - Muntaka Dahiru; Nor Kartini Abu Bakar; Ismail Yus off; Kah Hin Low; Muhammad N. Mohd (Environmental Monitoring and Assessment, 2020)

Synthesis, α-amylase inhibition and molecular docking study of bisindolylmethane sulfonamide derivatives - Muhammad Taha; Tayyaba Noreen; Syahrul Imran; Fasial Nawaz; Sridevi Chigurupati; Manikandan Selvaraj; Fazal Rahim; Nor Hadiani Ismail; Ashok Kumar; Ashik Mosaddik; Abdullah M. Alghamdi; Yousif Abdulrahman nasser alqahtani; et al. (Medicinal Chemistry Research, 2019)

An overview of climate change and variability impact studies in Nigeria - Da’u Abba Umar; Mohammad Firuz Ramli; Ahmad Zaharin Aris; Wan Nor Azmin Sulaiman; Muhammad Amar Zaudi; Abubakar Ibrahim Tukur (Arabian Journal of Geosciences, 2019)

Combustion performance and exhaust emissions fuelled with non-surfactant water-in-diesel emulsion fuel made from different water sources - Mohamad Azrin Ahmad; Wira Jazair Yahya; Ahmad Muhsin Ithnin; AK Hasannuddin; Muhammad Aiman Abu Bakar; Abdul Yasser Abd Fatah; Nor Azwadi Che Sidik; Hirofumi Noge (Environmental Science and Pollution Research, 2018)

Biochemical and structural characterization of a novel cold-active esterase-like protein from the psychrophilic yeast Glaciozyma antarctica - Noor Haza Fazlin Hashim; Nor Muhammad Mahadi; Rosli Md Illias; Shevin Rizal Feroz; Farah Diba Abu Bakar; Abdul Munir Abdul Murad (Extremophiles, 2018)

Structure Prediction of a Novel Exo-β-1,3-Glucanase: Insights into the Cold Adaptation of Psychrophilic Yeast Glaciozyma antarctica PI12 - Salimeh Mohammadi; Sepideh Parvizpour; Jafar Razmara; Farah Diba Abu Bakar; Rosli Md Illias; Nor Muhammad Mahadi; Abdul MunirAbdul Murad (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Suppression of PGE2 production via disruption of MAPK phosphorylation by unsymmetrical dicarbonyl curcumin derivatives - Mohd Fadhlizil Fasihi Mohd Aluwi; Kamal Rullah; Md. Areeful Haque; Bohari M. Yamin; Waqas Ahmad; Muhammad Wahab Amjad; Sze Wei Leong; Nurul Amira Fahmizar; Juriyati Jalil; Faridah Abas; Nor Hadiani Ismail; Ibrahim Jantan; et al. (Medicinal Chemistry Research, 2017)

Chemical speciation and bioavailability of rare earth elements (REEs) in the ecosystem: a review - Aysha Masood Khan; Nor Kartini Abu Bakar; Ahmad Farid Abu Bakar; Muhammad Aqeel Ashraf (Environmental Science and Pollution Research, 2017)

Retraction Note to: Release, deposition and elimination of radiocesium (137Cs) in the terrestrial environment - Muhammad Aqeel Ashraf; Ayesha Masood Khan; Mushtaq Ahmad; Shatirah Akib; Khaled S. Balkhair; Nor Kartini Abu Bakar (Environmental Geochemistry and Health, 2017)

Synthesis of 2-phenyl-1H-imidazo[4,5-b]pyridine as type 2 diabetes inhibitors and molecular docking studies - Muhammad Taha; Nor Hadiani Ismail; Syahrul Imran; Izzatul Ainaa; Manikandan Selvaraj; Mohd syukri baharudin; Muhammad Ali; Khalid Mohammed Khan; Nizam Uddin (Medicinal Chemistry Research, 2017)

Spatial distribution of natural γ radiation exposure and its relationship to soil types - Ahmad Termizi Ramli; Mohammad Syazwan Mohd Sanusi; Muhammad Hisyam Lee; Sallehuddin Sahrone; Nor Zati Hani Abu Hanifah (Natural Hazards, 2016)

Photocatalytic CO2 conversion over Au/TiO2 nanostructures for dynamic production of clean fuels in a monolith photoreactor - Beenish Tahir; Muhammad Tahir; Nor Aishah Saidina Amin (Clean Technologies and Environmental Policy, 2016)

Syntheses, in vitro evaluation and molecular docking studies of 5-bromo-2-aryl benzimidazoles as α-glucosidase inhibitors - Tanzila Arshad; Khalid Mohammed Khan; Najma Rasool; Uzma Salar; Shafqat Hussain; Tehreem Tahir; Mohammed Ashraf; Abdul Wadood; Muhammad Riaz; Shahnaz Perveen; Muhammad Taha; Nor Hadiani Ismail (Medicinal Chemistry Research, 2016)

Erratum to: Production of an oligosaccharide-specific cellobiohydrolase from the thermophilic fungus Thielavia terrestris - James Sy-Keen Woon; Mukram Mohamed Mackeen; Amirul Husna bin Sudin; Nor Muhammad Mahadi; Rosli Md Illias; Abdul Munir Abdul Murad; Farah Diba Abu Bakar (Biotechnology Letters, 2016)

Production of an oligosaccharide-specific cellobiohydrolase from the thermophilic fungus Thielavia terrestris - James Sy-Keen Woon; Mukram Mohamed Mackeen; Amirul Husna bin Sudin; Nor Muhammad Mahadi; Rosli Md Illias; Abdul Munir Abdul Murad; Farah Diba Abu Bakar (Biotechnology Letters, 2016)

Synthesis of 2-(2-methoxyphenyl)-5-phenyl-1,3,4-oxadiazole derivatives and evaluation of their antiglycation potential - Muhammad Taha; Nor Hadiani Ismail; Waqas Jamil; Syahrul Imran; Fazal Rahim; Syed Muhammad Kashif; Mohd Zulkefeli (Medicinal Chemistry Research, 2016)

Synthesis and evaluation of unsymmetrical heterocyclic thioureas as potent β-glucuronidase inhibitors - Muhammad Taha; Nor Hadiani Ismail; Waqas Jamil; Khalid Mohammed Khan; Uzma Salar; Syed Muhammad Kashif; Fazal Rahim; Yawar Latif (Medicinal Chemistry Research, 2015)

Erratum to: Synthesis crystal structure of 2-methoxybenzoylhydrazones and evaluation of their α-glucosidase and urease inhibition potential - Muhammad Taha; Nor Hadiani Ismail; Mohd Syukri Baharudin; Salima Lalani; Sadia Mehboob; Khalid Mohammed Khan; Sammer Yousuf; Salman Siddiqui; Fazal Rahim; M. Iqbal Choudhary (Medicinal Chemistry Research, 2015)

Synthesis crystal structure of 2-methoxybenzoylhydrazones and evaluation of their α-glucosidase and urease inhibition potential - Muhammad Taha; Nor Hadiani Ismail; Mohd Syukri Baharudin; Salima Lalani; Sadia Mehboob; Khalid M. Khan; Sammer yousuf; Salman Siddiqui; Fazal Rahim; M. Iqbal Choudhary (Medicinal Chemistry Research, 2015)

Assessment of groundwater vulnerability to anthropogenic pollution and seawater intrusion in a small tropical island using index-based methods - Nura Umar Kura; Mohammad Firuz Ramli; Shaharin Ibrahim; Wan Nor Azmin Sulaiman; Ahmad Zaharin Aris; Adamu Idris Tanko; Muhammad Amar Zaudi (Environmental Science and Pollution Research, 2015)

Synthesis of indole-2-hydrazones in search of potential leishmanicidal agents - Muhammad Taha; Nor Hadiani Ismail; Muhammad Ali; Khalid M. Khan; Waqas Jamil; Syed Muhammad Kashif; Mohammad Asraf (Medicinal Chemistry Research, 2014)

RETRACTED ARTICLE: Release, deposition and elimination of radiocesium (137Cs) in the terrestrial environment - Muhammad Aqeel Ashraf; Ayesha Masood Khan; Mushtaq Ahmad; Shatirah Akib; Khaled S. Balkhair; Nor Kartini Abu Bakar (Environmental Geochemistry and Health, 2014)

Molecular cloning, expression and characterisation of Afp4, an antifreeze protein from Glaciozyma antarctica - Noor Haza Fazlin Hashim; Suhaila Sulaiman; Farah Diba Abu Bakar; Rosli Md Illias; Hidehisa Kawahara; Nazalan Najimudin; Nor Muhammad Mahadi; Abdul Munir Abdul Murad (Polar Biology, 2014)

Thermal stress responses in Antarctic yeast, Glaciozyma antarctica PI12, characterized by real-time quantitative PCR - Sook Yee Boo; Clemente Michael Vui Ling Wong; Kenneth Francis Rodrigues; Nazalan Najimudin; Abdul Munir Abdul Murad; Nor Muhammad Mahadi (Polar Biology, 2013)

Characterization of Afp1, an antifreeze protein from the psychrophilic yeast Glaciozyma antarctica PI12 - Noor Haza Fazlin Hashim; Izwan Bharudin; Douglas Law Sie Nguong; Sakura Higa; Farah Diba Abu Bakar; Sheila Nathan; Amir Rabu; Hidehisa Kawahara; Rosli Md. Illias; Nazalan Najimudin; Nor Muhammad Mahadi; Abdul Munir Abdul Murad (Extremophiles, 2013)

A mutant l-asparaginase II signal peptide improves the secretion of recombinant cyclodextrin glucanotransferase and the viability of Escherichia coli - Noor Faizah Ismail; Salehhuddin Hamdan; Nor Muhammad Mahadi; Abdul Munir Abdul Murad; Amir Rabu; Farah Diba Abu Bakar; Peter Klappa; Rosli Md. Illias (Biotechnology Letters, 2011)

Expression and characterization of Trichoderma virens UKM-1 endochitinase in Escherichia coli - Nadiawati Alias; Nor Muhammad Mahadi; Abdul Munir Abdul Murad; Farah Diba Abu Bakar; Nik Azmi Nik Mahmood; Rosli Md Illias (World Journal of Microbiology and Biotechnology, 2009)

Antinociceptive, anti-inflammatory, and antipyretic properties of an aqueous extract of Dicranopteris linearis leaves in experimental animal models - Zainul Amiruddin Zakaria; Zuleen Delina Fasya Abdul Ghani; Raden Nur Suraya Raden Mohd. Nor; Hanan Kumar Gopalan; Mohd. Roslan Sulaiman; Abdul Manan Mat Jais; Muhammad Nazrul Somchit; Arifah Abdul Kader; Johari Ripin (Journal of Natural Medicines, 2008)